If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 = g + 1 Reorder the terms: 4 = 1 + g Solving 4 = 1 + g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. 4 + -1g = 1 + g + -1g Combine like terms: g + -1g = 0 4 + -1g = 1 + 0 4 + -1g = 1 Add '-4' to each side of the equation. 4 + -4 + -1g = 1 + -4 Combine like terms: 4 + -4 = 0 0 + -1g = 1 + -4 -1g = 1 + -4 Combine like terms: 1 + -4 = -3 -1g = -3 Divide each side by '-1'. g = 3 Simplifying g = 3
| (x^2)-x+1=0 | | 2(A+4)=11.2 | | (x^2)-5x=6 | | 4n-30=26 | | 0.3-0.03(x+1)=-0.05(1-x) | | 3(x+5)=-12 | | 3x-9y=54 | | -13n+14=40 | | 12y+4=8 | | 5x+8y=16 | | 2x+7+28=4x | | 1/2ln(y-1)-1/2ln(y+1)=1/2ln(x-1)-1/2ln(x+1) | | 4-(1/x)-(2/(x^2))=0 | | -3.3y=21.7 | | (3/4x^2)-(1/4x)-(1/2)=0 | | 12(2w-5)=4(6w+10) | | 20+8*0.5/20-x=12 | | 33-2x=6x+5 | | 7x+28=7x-14 | | -2x+6=-18+x | | 5(x+6)=40 | | (3x+40)+(2x-10)=180 | | -8y^2+4y-14=0 | | 6x-48+4x+9=180 | | 11a=0.088 | | 6E-3=25.2 | | y^4-33y^2+256=0 | | 6x-9+3x+24=180 | | 1/8=y/5 | | y^2+256/y^2=32 | | 2(4x-6y)= | | 9x-8=90 |